P57Kip2 knock‐in mouse reveals CDK‐independent contribution in the development of Beckwith–Wiedemann syndrome. Issue 3 (4th May 2016) - Duquesnes, Nicolas; Callot, Caroline; Jeannot, Pauline; Daburon, Virginie; Nakayama, Keiichi I; Manenti, Stephane; Davy, Alice; Besson, Arnaud
Abstract: CDKN1C encodes the cyclin–CDK inhibitor p57 Kip2 (p57), a negative regulator of the cell cycle and putative tumour suppressor. Genetic and epigenetic alterations causing loss of p57 function are the most frequent cause of Beckwith–Wiedemann syndrome (BWS), a genetic disorder characterized by multiple developmental anomalies and increased susceptibility to tumour development during childhood. So far, BWS development has been attributed entirely to the deregulation of proliferation caused by loss of p57‐mediated CDK inhibition. However, a fraction of BWS patients have point mutations in CDKN1C located outside of the CDK inhibitory region, suggesting the involvement of other parts of the protein in the disease. To test this possibility, we generated knock‐in mice deficient for p57‐mediated cyclin–CDK inhibition (p57 CK – ), the only clearly defined function of p57. Comparative analysis of p57 CK – and p57 KO mice provided clear evidence for CDK‐independent roles of p57 and revealed that BWS is not caused entirely by CDK deregulation, as several features of BWS are caused by the loss of CDK‐independent roles of p57. Thus, while the genetic origin of BWS is well understood, our results underscore that the underlying molecular mechanisms remain largely unclear. To probe these mechanisms further, we determined the p57 interactome. Several partners identified are involved in genetic disorders with features resembling those caused by CDKN1C mutation, suggesting that they could be involved in BWS pathogenesis and revealing a possible connection between seemingly distinct syndromes. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.